SrGAP1 mediates the migration inhibition effect of Slit2-Robo1 in colorectal cancer. Issue 1 (December 2016) - Feng, Yuyang; Feng, Lei; Yu, Di; Zou, Jian; Huang, Zhaohui
Abstract Background The neuronal guidance molecule Slit2 plays suppressive role in tumorigenesis and progression. We previously showed that Slit2-Robo1 inhibit cell migration in colorectal cancer (CRC). However, little is known about its downstream effectors in CRC. This study tries to identify whether the Slit-Robo Rho GTPase activating protein 1 (srGAP1) could mediate the inhibitory effect of Slit2-Robo1 on CRC cell migration. Methods The protein expression of srGAP1 in clinical CRC tissues was tested by immunohistochemistry staining. Conditioned medium was prepared from HEK293 cells stably expressing Slit2-myc, Robo1-HA or RoboN (a soluble extracellular domain of Robo1). Immunoprecipitation (IP) was applied to check the interaction between Robo1 and srGAP1, and immunofluorescence (IF) was used to observe the subcellular localization of Robo1 and srGAP1. Small GTPase pull-down assay was used to determine the activity of Cdc42. A modified wound healing assay was performed to detect cell migration. Results The protein expression of srGAP1 was remarkably decreased in 47.5% of CRC tissues compared with adjacent noncancerous tissues, and the decreased srGAP1 expression was associated with lymphatic invasion, poor tumor differentiation, high TNM stage, and poor survival (P < 0.05). IP and IF assays revealed that srGAP1 was a Robo1-interacting protein and exhibited similar dynamic subcellular distribution after Slit2 treatment in CRC cells. Small GTPase pull-down assay and migration assay indicated that Slit2-Robo1 signaling inhibited Cdc42 activity and CRC cell motility through srGAP1. Conclusion Downregulation of srGAP1 in CRC was associated with tumor progression and poor prognosis. srGAP1 is an important downstream molecule of Slit2 signalling in CRC, and mediates the anti-migration function of Slit2 by inhibiting Cdc42.